Political Trust and Aspirations to Influence Social Media During a Crisis: A Longitudinal Study - Koivula, Aki; Malinen, Sanna; Koiranen, Ilkka (Wiley, 2026)
This study investigated how political trust shaped citizens' aspirations to influence others on social media during a COVID-19 pandemic. Using four-wave longitudinal survey data (2017–2021; N = 2172) collected from 543 citizens in Finland, we first analysed how political trust moderated the temporal development of individuals' aspirations to influence others online. We then examined how trust and influence aspirations jointly contributed to citizens' social media behaviour during the COVID-19 pandemic. The findings showed that aspirations to influence declined during the crisis, particularly among those with high political trust. In contrast, individuals with low trust typically maintained their influence aspirations and were more likely to engage on social media and to criticise public authorities. High political trust, on the other hand, did not promote criticism but was instead positively associated with support. Overall, these findings clarify social media engagement dynamics in times of crisis and the tendency of online discussions to amplify the voices of those who are politically frustrated or sceptical. From a policy perspective, the results highlight how trust asymmetries shape visible participation in digital spaces, offering evidence relevant to the design of crisis communication, platform governance, and strategies for engaging both vocal critics and less visible, high-trust citizens.